FACTORS AFFECTING TO ORGANIC FOOD BUYING INTENTION - Abeyrathna, K.G.N.W. (International Journal of Research -GRANTHAALAYAH, 2021)
Organic food is one latest food cultures of Sri Lankan community due to the non-communicable diseases of the inorganic foods. After the green revolution and plantation culture of the country farmers used to use the pesticides, Insecticides, , Fungicides to manage the crops. After the green revolution, multinational companies who are based on the Monsanto concept started to distribute their chemicals under the faith of high yield. Today Sri Lanka is the country which has the most agriculture based chemical consumers in the world.